An assessment of chemotherapy-induced nausea and vomiting direct costs in three EU countries - Marco Turini; Vittoria Piovesana; Pierfrancesco Ruffo; Claudio Ripellino; Nazarena Cataldo (BioExcel Publishing Ltd, 2015)
Background: Chemotherapy-induced nausea and vomiting (CINV) has been commonly reported as one of the most distressing adverse effects among treated patients with cancer. Inadequately treated, CINV can lead to increased resource utilization and severely impair patients' daily functioning and quality of life. Direct costs include acquisition cost of antiemetic drugs and rescue medication, administration devices, add-on treatments, such as hydration, and additional patient care, that is, nursing and physician time, unscheduled office visits, emergency room admissions, and, in some cases, extended hospitalization or readmission. There are many reports on the cost-effectiveness of antiemetic drugs, but information on the total cost per patient associated with CINV is limited. The costs associated with severe CINV episodes are considered responsible for the most significant part of the expenditures. Scope: The aim of this study was to investigate the management of CINV episodes in three European health-care environments and to estimate direct costs associated with severe CINV episodes. Methods: An online survey addressed to Italian, German, and French oncologists and oncology nurses was performed. The survey included 41 questions about the management and the resource utilization for patients experiencing any CINV episode during the 6-month period preceding the survey. Furthermore, the cost associated with severe CINV episode management was estimated by adopting the National Health Service's perspective. Findings: A large proportion of patients receiving chemotherapy experienced a CINV episode (34.4% in Italy, 50.2% in France, and 40.4% in Germany); among those, 8.8% in Italy, 11.6% in France, and 19.2% in Germany experienced a severe CINV episode. Compared with Italy, Germany and France presented a greater hospitalization rate following an unplanned visit to the oncology ward or an emergency room access due to CINV. In Italy, the mean cost per patient with a severe CINV episode resulted in approximately €389, about half of the mean cost in France (€750) and a third of the mean cost in Germany (€1,017). Conclusions: Severe CINV episodes requiring hospitalization, day hospital, or hospitalization extension involve a significant cost for the National Health Services; additional studies should be conducted in order to evaluate potential ways to offset these expenses.